The Checklist of sauria in the “Pedro Franco Dávila” Scientific Station (Los Ríos-Ecuador), during may to september 2015 (Revista Científica Ciencias Naturales y Ambientales, 2016)
A checklist and morphological description of 11 species of sauria recorded in the Pedro Franco Dávila Scientific Station, located in Jauneche precint, province of Los Ríos, is presented here. Fieldwork was achieved between May and September 2015. Direct search technique and visual observation in all types of microhabitats and vegetation such as trees, dry trunks, leaf litter, among others were used. As a result, 68 individuals were collected, those belonging to six families, six genera and 11 species. Regarding to the diversity at generic level: Anolis (Dactyloidae) is represented by three species; Gonatodes (Sphaerodactylidae), Holcosus (Teiidae) and Stenocercus (Tropiduridae), each one has two species; Alopoglossus (Gymnophthalmidae) and Iguana (Iguanidae) are represented by one species, respectively. Gonatodes is the most abundant genus, comprising G. caudisculatus and G. concinatus in the interior of forest, those representing 44 and 22%, respectively. At the outer area of forest, Holcosus septemlineata was the most abundant species recording 40%; that area contains the highest diversity of sauria.
Keywords: Ameiva; Anolis; herpetofauna; lizzards; sauria